IMPLEMENTATION OF MITIGATION PROGRAM OF CHILD WORKERS IN BANDUNG CITY - Yuyun - Yuningsih; Sumardani - (Lembaga Penelitian Universitas Pasundan, 2018)
Child workers arean important issue related to the human right for children. The right of a child who works is taken when she works for the parent’s interest. The issue of child workers is not only caused by the child but also by the external factors of herself. Social environment influence has a strong effect to the child’s decision to enter into labor force.To attain such goal, empowerment approach is used based on the assumption that child workersbecome problematic whenshe has no capacity to self-organize (self-organization) and defend her rights and interests. Programs related to welfare, aid support, rule-making, and direct service to society,in essence are perceived as human actions aimed at helping a group of people who are less fortune, to gain social function, particularly for child workers.Data analyses are descriptive and qualitative. Research result showed thataid support program for child workers in Bandung is done through prevention, rehabilitation and empowerment which involved stakeholders fromagency, government institution and private party as well as society in Bandung. They have participated in the effort to abolish child labor, but they need to improve the coordination comprehensively.